Lateral Earth Pressure Analysis for Gabion Retaining Wall Structure Design with Geogrid Optimisation: A Numerical Study - zamri, ikhwan; Salina Sani; Chee Ming Chan (Progress in Engineering Application and Technology, 2024)
Developing sustainable and economically earth retaining structures become essential, especially in the context of urbanization and infrastructure development. Ensuring the safety of these structures is a major concern in geotechnical engineering. This research addresses the failure modes of natural clay slopes and backfill, emphasizing the need for effective gabion retaining walls to prevent collapse. Using PLAXIS 2D finite element software, the study models the interaction between soil and gabion structures, analysing lateral earth pressure distribution and vertical displacement. Objectives of this study include evaluating structural response towards lateral pressure and displacement occurred, optimizing gabion retaining wall designs, and comparing FEM results with manual calculations. This study explores two solutions for enhancing gabion retaining wall performance: testing different vertical layers to determine the most optimise design for retaining an 8-meter height of backfill and examining the use of geogrid reinforcement in the soil backfill under various loading conditions. The result is the step-looking gabion retaining wall is the most optimise structure to be used and can retain the soil backfill due to acceptable limit for vertical displacement and low lateral effective earth pressure occurred on gabion retaining wall.